Primary Amine–2-Aminopyrimidine Chiral Organocatalysts for the Enantioselective Conjugate Addition of Branched Aldehydes to Maleimides - Vízcaíno-Milla, Pascuala; Sansano, José M.; Nájera, Carmen; Fiser, Béla; Gómez-Bengoa, Enrique (Synthesis, 2015)
Chiral primary amines containing the (R,R)- and (S,S)-trans-cyclohexane-1,2-diamine scaffold and a pyrimidin-2-yl unit are synthesized and used as general organocatalysts for the Michael reaction of α-branched aldehydes to maleimides. The reaction takes place with 10 mol% organocatalyst loading and hexanedioic acid as cocatalyst in aqueous N,N-dimethylformamide at 10 °C affording the corresponding succinimides in good yields and enantioselectivities. DFT calculations support the stereochemical results and the role played by the solvents.
Keywords: asymmetric organocatalysis; maleimides; succinimides; aldehydes; Michael addition